On the issue of some historical military names. (Eurasian Journal of Philology Science and Education, 2015)
This article considers ideas of language nature of some obsolete words (historical) army words, used by Kazakh people in the military methods and defense of their homeland, land, independence, and also it considers the names of military weapon, names of military uniform used at that time and preserved up to present constituting the richest vocabulary fund of the mother tongue. In the historical military descriptions, words and phrases that can be found in the oral folk heritage, and the Kazakh military vocabulary takes the main place. The Kazakh national military terminology considered in the article was formed within the frame of terms development in their language unity. Even today, some military obsolete words used in the Kazakh epos, heroic stories (songs), are found in the military vocabulary. This is the reason of the analysis of their meanings and examples of usage. At the given article the author shares and proves opinions of the scholars whose research is devotedto the Kazakh oral folk art. According to their view, some obsolete historical military words-terms are used while applying military methods.
Keywords: intelligence officer; military drummer; straight fight; belt; waist belt; sword knot; army; forced; warrior